Sari Buah Lontar Sebagai Pengencer Alami Dalam Mempertahankan Kualitas Spermatozoa Babi - Nancy D. F. K. Foeh; Cynthia D. Gaina (JURNAL KAJIAN VETERINER, 2019)
The aim of this study was to investigate the effect of Siwalan Palm Juice as a natural extender for maintaining boar sperm quality. Semen ejaculates collected from three Duroc and Landrace boars were macroscopically (volume, colour, odor, pH and consistency) and microscopically (motility, concentration and abnormality) evaluated. Semen samples fulfilled all criteria for semen characteristic (motility > 70%, concentration 200 x 106 cells /ml and abnormality ≤ 20%). Antibiotics were added in this semen samples. This study used completely randomized design with 6 treated groups, each group repeated three times. K0 (control): fresh semen; K1: Siwalan juice + Landrace boar semen; K2: Coconut water + Landrace boar semen; K3: NaCL + Landrace boar semen; K4: Siwalan juice + Duroc boar semen; K5: Coconut water + Duroc boar semen; K6: NaCL + Duroc boar semen. This semen samples were stored under room temperature at 220C. The result shows that Duroc and Landrace boar spermatozoa can be stored in Siwalan Palm Juice extender for up to 24 hours. It can concluded that Siwalan Juice could be used as one of natural extender for maintaining boar sperm quality under room temperature at 220C.